Permasalahan Credit Crunch Perbankan Syariah Di Indonesia Ditinjau Dari Tawhidi String Relation - Khodijah Ishak; Muhammad Isa Selamat; Kiki Candri; Muhammad Fadhil Junery; Siswati Siswati (JPS (Jurnal Perbankan Syariah), 2022)
This study aims to show the problem of the credit crunch in Islamic banking in Indonesia from the perspective of Tawhidi String Relation (TSR). This research is a literature review using library data. The study results show that the main problems that trigger the emergence of a credit crunch in Islamic banking in Indonesia are natural disasters and the lack of availability of Islamic banking capital. Religious values have become a concept and a reference for every Islamic banking activity in Indonesia, which is based on the Al-Quran and Hadith. This research can be used as a reference for increasing the productivity of Islamic banking in maintaining the stability of the national economy. Practically this research can be a basis that can be applied universally in achieving benefits for all people.